Diffusion and conformational dynamics in locally perturbed model membrane systems - Petrov, Eugene P.; Schwille, Petra (Diffusion Fundamentals, 2015)
In this article, we review our results on diffusion and phase separation in lipid membranes, as well as on interaction of membranes with colloidal particles, biomacromolecules, and supramolecular assemblies, which were obtained within the framework of the Saxon Research Unit FOR 877 “From Local Constraints to Macroscopic Transport”.